GERAKAN PEMIKIRAN SAYYID AHMAD KHAN DI INDIA SEBAGAI USAHA MENGUBAH PEMIKIRAN ISLAM - Hamlan, Hamlan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Sayyid Ahmad Khan is a reformist of Islamic thought in India was born in October 17th 1817 and passed away in March 27th 1898. He was a reformer who afforded to change the level of life and form of thought of MuslimÂ  from traditional to modern one.